Negative marital interaction, purpose in life, and depressive symptoms among middle-aged and older couples: evidence from the Health and Retirement Study. (3rd April 2022) - Irani, Elliane; Park, Sumin; Hickman, Ronald L.
Abstract: Objective: Negative marital interaction and purpose in life have been associated with depressive symptoms. Yet, these associations have not been fully explored in a dyadic context. This study examines the actor (intra-individual) and partner (cross-spousal) effects of negative marital interaction on depressive symptoms in couples and the potential mediating role of purpose in life. Methods: Data came from 1186 heterosexual married couples who participated in the 2016 (T1) and 2018 (T2) waves of the Health and Retirement Study and completed the psychosocial questionnaire in 2016. Structural equation modeling was used to estimate the direct and indirect associations among T1 negative marital interaction, T1 purpose in life, and T2 depressive symptoms at the actor and partner levels. Models controlled for age, race, educational level, self-rated health, and length of marriage. Results: At the actor level, a greater negative marital interaction was associated with significantly lower levels of purpose in life for husbands and wives. Negative marital interaction was also associated with depressive symptoms for wives. Purpose in life mediated the relationship between negative marital interaction and depressive symptoms. At the partner level, wives' negative marital interaction was negatively associated with husbands' purpose in life, independent of husbands' own effects. Conclusion: The findings support the dominant marital discord model of depression and highlight gender differences in the cross-spousal effects of negative marital interaction on purpose in life. Positive psychology interventions can be beneficial to promote purpose in life and subsequently improve mental health outcomes among couples.